Laser system of microwave picosecond pulse trains used for emission initiation in the photogun - Dyomin, V.S.; Dovbnya, A.N.; Reprintsev, L.V.; Shendrik, V.A. (Вопросы атомной науки и техники, 2006)
The scheme of picosecond pulse train formation by scanning of a laser ray across the adjustable diaphragm by
means of a microwave traveling-wave optical deflector is presented. After amplification and conversion these pulses
can be used for photoemission obtaining in photoguns. Представлена схема формирования серии пикосекундных оптических импульсов путем сканирования лазерного луча с помощью СВЧ-дефлектора бегущей волны по регулируемой диафрагме. После усиления и преобразования эти импульсы можно использовать для получения эмиссии в фотопушках. Приведена схема формування серії пікосекундних оптичних імпульсів шляхом сканування лазерного
променя за допомогою НВЧ-дефлектора бігучої хвилі по діафрагмі, що регулюється. Після підсилення і
перетворення ці імпульси можна використовувати для одержання емісії в фотогарматах.